Halls of Lost (and Found) Causes: Retracing Jewish exile, trauma and memory in W. G. Sebald's Austerlitz (2001) and The Emigrants (1996) - Fraser-Smith, Ross (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
This dissertation approaches W. G. Sebald's prose works, specifically the narratives The Emigrants (1996) and Austerlitz (2001), through an analysis focusing on Sebald's representation of Jewish exile identity in a post-war European context. The extent to which Sebald successfully reconstructs Jewish memory in the present is my point of departure in this dissertation. As I argue, these travel narratives represent the ambivalence of post-war Jewish exile identity and its associated trauma through the journey as a 'methodology of memory'. I contend that the imaginary, discursive and liminal space created through the mediation of memory enables a reconstruction of Jewish cultural memory in the present. This deconstructs various cultural binaries and is accounted for on three distinct levels. Firstly, as an uncanny figure, travel blurs the familiar and foreign and problematises the notion of an enclosed, rooted Heimat. Secondly, as a narrative device, it engages with issues of historical mediation by overlaying multiple historical frames and connecting disparate sites of memory, thus blurring history and memory, place and 'non-place' (Marc AugÃ©). As I show, this also allows for 'postmemorial' (Marianne Hirsch) and intercultural dialogue to be established between disparate subjects through the sharing of memory. Finally, as a symbol of Jewish exile identity, travel is engaged as its own symbolic 'lieu de mémoire' (Pierre Nora), which, bearing the traces of Jewish dispersion, operates as both a destructive and productive force. I argue that this threefold figurative, narrative and symbolic form offers an ethical representation of the ambivalent status of post-war Jewish exile, suspended between the poles of cultural integration in a foreign place and the desire to return to a lost homeland. This said, both texts construct Jewish exile identity as a dialectic process, formed of both destructive and constructive memories. Travel is therefore a symbol of both dislocation and absent identity, but also an important means of identity formation.
Keywords: Identities and Cultures of Europe